Cortisol levels and depression suicide risk: a combined exploration of meta-analysis and case-control study - Zhaowei Jiang; Liying Dong; Yajie Zhang; Hongjing Mao; Fugang Luo; Mingfen Song (Frontiers in Psychiatry)
ObjectiveTo evaluate the association between cortisol levels and suicide in patients with depression through a meta-analysis to provide an early warning for suicide prevention.MethodsDatabases including China National Knowledge Infrastructure (CNKI), Weipu Database (VIP), Wanfang Database, PubMed, Cochrane Library, Web of Science, and Embase were searched to collect case-control studies, cohort studies, and cross-sectional studies investigating the relationship between cortisol levels and suicide in patients with depression. The meta-analysis was conducted using Stata 18.0. Meanwhile, we collected data from 131 participants to measure their cortisol levels, including Hair cortisol levels (HCL) were calculated for the 0–1 cm and 1–2 cm segments.ResultsThe meta-analysis indicated that cortisol levels in depressed patients with suicidal behavior were significantly higher than healthy individuals (SMD = 0.350, 95% CI [0.003, 0.696]). However, the cortisol levels in patients with suicidal behavior were only slightly higher than those in patients without suicidal behavior, and the pooled effect size (SMD = 0.108, 95% CI [-0.151, 0.367]) was non-significant. The depression patients with suicidal behaviors had significantly lower levels of 0–1 cm HCL (3.46 ± 1.92 ng/mg) than those in the depression patients without suicidal ideation (5.43 ± 2.42 ng/mg) (P=0.003) and in the depression patients with suicidal ideation (5.04 ± 2.30 ng/mg) (P=0.037). Similarly, 1–2 cm HCL was significantly lower in the depression with suicidal behavior group (3.21 ± 1.47 ng/mg) than in the depression without suicidal ideation group (5.65 ± 3.59 ng/mg) (P=0.009) and in the depression with suicidal ideation group (5.10 ± 2.88 ng/mg) (P=0.050).ConclusionThe study found that cortisol levels in patients with depression who exhibited suicidal behavior were higher than those in the healthy population. However, no significant difference in cortisol levels was observed between patients with depression and suicidal behavior and those without suicidal behavior. The experiment revealed that patients with depression and suicidal behavior had lower hair cortisol levels (HCL) than those depression without suicidal behavior.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024609538, identifier CRD42024609538.